HARVEY, ANAMARÍA (Comp.) (2005). En torno al discurso. Contribuciones de América Latina. Santiago de Chile: Ediciones Universidad Católica de Chile. 359 pp. ISBN 956-14-0805-8 - Peronard Thierry, Marianne (Revista Latinoamericana de Estudios del Discurso, 2021)
HARVEY, ANAMARÍA (Comp.) (2005). En torno al discurso. Contribuciones de América Latina. Santiago de Chile: Ediciones Universidad Católica de Chile. 359 pp. ISBN 956-14-0805-8.